2013
DOI: 10.1093/ndt/gfs525
|View full text |Cite
|
Sign up to set email alerts
|

New strategy of α- and γ-tocopherol to prevent contrast-induced acute kidney injury in chronic kidney disease patients undergoing elective coronary procedures

Abstract: Prophylaxis administration with oral α- or γ-tocopherol in combination with 0.9% saline is effective in protecting against CI-AKI in CKD patients undergoing elective coronary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 42 publications
0
69
2
4
Order By: Relevance
“…While the protective effect of vitamin E against AKI was first reported over 20 years ago, since then the therapeutic action of vitamin E has been demonstrated in many different animals (including mice [16,21], rats [13,22,23], rabbits [14], dogs [24], and pigs [25]) by using a variety of modeling methods (including ischemia/reperfusion [14,26,27], cisplatin [25,28], and other methods [13,29,30]), and has even been demonstrated in clinical studies [31,32] (Supplementary Table 1. Detailed information on the AKI models applied in the investigation of the protective effect of vitamin E).…”
Section: Therapeutic Action Of Vitamin E Against Akimentioning
confidence: 99%
See 1 more Smart Citation
“…While the protective effect of vitamin E against AKI was first reported over 20 years ago, since then the therapeutic action of vitamin E has been demonstrated in many different animals (including mice [16,21], rats [13,22,23], rabbits [14], dogs [24], and pigs [25]) by using a variety of modeling methods (including ischemia/reperfusion [14,26,27], cisplatin [25,28], and other methods [13,29,30]), and has even been demonstrated in clinical studies [31,32] (Supplementary Table 1. Detailed information on the AKI models applied in the investigation of the protective effect of vitamin E).…”
Section: Therapeutic Action Of Vitamin E Against Akimentioning
confidence: 99%
“…Prophylaxis adminLVWUDWLRQ ZLWK RUDO Į-WRFRSKHURO RU Ȗ-tocopherol in combination with saline has been shown to be effective against CI-AKI in patients. Moreover, IXUWKHU FOLQLFDO UHVXOWV KDYH LQGLFDWHG WKDW Į-tocopherol produces a more significant effect than Ȗ-tocopherol when compared with the placebo group [31]. Most significantly, although the results of these early human trials still need to be further confirmed through adequately powered randomized controlled studies, these clinical studies mark the beginning of an extraordinary period in vitamin E-based therapy against AKI.…”
Section: Therapeutic Action Of Vitamin E Against Akimentioning
confidence: 99%
“…Su et al had identified 3 randomized trials on vitamin E prophylaxis against CIAKI (3)(4)(5). We pooled the results of these 3 studies (Figure 1) and calculated a pooled estimate of RR = 0.38 (95% CI 0.24-0.62), indicating that vitamin E significantly prevented CIAKI.…”
Section: To the Editormentioning
confidence: 97%
“…Bu konuda yapılan in vitro bir çalışmada böbrek hücresinde, EPA ve DHA'nın, PPARγ bağımlı bir yolak üzerinden, nükleer faktör kappa b (NF-κB) aktivasyonunu ve MCP-1 ekspresyonunu anlamlı şekilde azalttığı gösterilmiştir (52). Kronik böbrek hastalarında (son evre hariç) koroner girişim sonrasında gelişebilecek akut böbrek hasarının önlenmesinde α-tokoferol ve γ-tokoferol suplemantasyonunun anlamlı etkisinin olduğu bir çalışmada bildirilmiştir (61)…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified